CeO2 - ZrO2 Catalysts for the Use of Biogas in IT-SOFC. (2nd June 2015) - Pappacena, Alfonsina; Graziutti, Rafael; Boaro, Marta; Trovarelli, Alessandro
Abstract : Ce0.8 Zr0.2 O2 and Ce0.8 La0.5 Nd0.2 Zr0.13 O2-x, were prepared with a surfactant assisted approach and impregnated with different amounts of nickel. The catalysts were studied in the dry reforming reaction with the aim of using them in a biogas fuelled IT-SOFC anode. The oxidative dry reforming reaction was also investigated, finding that small amounts of oxygen in the biogas mixture reduce the effect of dry reforming side reactions. Catalysts containing Lanthanum and Neodymium showed an improved activity at 600 °C and 650 °C in terms of H2 selectivity and carbon resistance.